AGFORWARD Project Final Report - Burgess, Paul J.; den Herder, Michael; Dupraz, Christian; Garnett, Kenisha; Giannitsopoulos, Michail; Graves, Anil; Hermansen, John E.; Kanzler, Michael; Liagre, Fabien; Mirck, J.; Moreno, Gerardo; Mosquera-Losada, María Rosa; et al. (Cranfield University, 2018)
Executive summary: The AGFORWARD project (Grant Agreement N° 613520) had the overall goal to promote agroforestry practices in Europe that will advance sustainable rural development. It had four objectives (described below) which address 1) the context and extent of agroforestry in Europe, 2) identifying, developing and field-testing agroforestry innovations through participatory networks, 3) evaluating innovative designs and practices at field-, farm-, and landscape-scales, and promoting agroforestry in Europe through policy development and dissemination. Agroforestry is defined as the practice of deliberately integrating woody vegetation (trees or shrubs) with crop and/or animal systems to benefit from the resulting ecological and economic interactions. Context: European agroforestry has been estimated to cover 10.6 Mha (using a literature review) and 15.4 Mha using the pan-European LUCAS dataset (i.e. 8.8% of the utilised agricultural area). Livestock agroforestry (15.1 Mha) is, by far, the dominant type of agroforestry. The LUCAS analysis provides a uniform method to compare agroforestry areas between countries and over time. Identify, develop and field-test agroforestry innovations: 40 stakeholder groups (involving about 820 stakeholders across 13 European countries) developed and field-tested agroforestry innovations which have been reported in 40 “lesson learnt” reports, and in a user-friendly format in 46 “Agroforestry innovation leaflets”. The innovations for agroforestry systems of high nature and cultural value included cheaper methods of tree protection and guidance for establishing legumes in wood pastures. Innovations for agroforestry with timber plantations, olive groves and apple orchards include the use of medicinal plants and reduction of mowing costs. Innovations for integrating trees on arable farms included assessments of yield benefits by providing wind protection. Innovations for livestock farms included using trees to enhance animal welfare, shade protection, and as a source of fodder. Peer-reviewed journal papers and conference presentations on these and other related topics were developed. Evaluation of agroforestry designs and practices at field- and landscape-scale: a range of publicly available field-scale analysis tools are available on the AGFORWARD website. These include the “CliPick” climate database, and web-applications of the Farm-SAFE and Hi-sAFe model. The results of field- and landscape-scale analysis, written up as peer-reviewed papers, highlight the benefits of agroforestry (relative to agriculture) for biodiversity enhancement and providing regulating ecosystem services, such as for climate and water regulation and purification. Policy development and dissemination: detailed reviews of existing policy and recommendations for future European agroforestry policy have been produced. The support provided is far wider than the single specified agroforestry measures. The recommendations included the collation of existing measures, and that agroforestry systems should not forfeit Pillar I payments. Opportunities for farmlevel and landscape-level measures were also identified. The project results can be found on the project website (www.agforward.eu), a Facebook account (www.facebook.com/AgforwardProject), a Twitter account (https://twitter.com/AGFORWARD_EU), and a quarterly electronic newsletter (http://www.agforward.eu/index.php/en/newsletters-1514.html). The number of national associations in Europe was extended to twelve, and a web-based training resource on agroforestry (http://train.agforward.eu/language/en/agforall/) created. AGFORWARD also supported the Third European Agroforestry Conference in Montpellier in 2016 attracting 287 delegates from 26 countries including many farmers. We also initiated another 21 national conferences or conference sessions on agroforestry, made about 240 oral presentations, 61 poster presentations, produced about 50 news articles, and supported about 87 workshop, training or field-visit activities (in addition to the stakeholder groups).
Keywords: Agroforestry; Research; Project; Europe; Land Use; Agriculture; Forestry; Stakeholder; Development; Co-ordination